Une macro-géographie du commerce de détail en Belgique - Jean-Pierre Grimmeau; Benjamin Wayens; Emilie Hanson (EchoGéo)
Thisarticleanalyzesanew source, followingacomprehensivefield inventory. ItconfirmsthatBelgiumhasadensecommercial equipmentcomparedto the countries of northwestern Europe. Itpresentsthemostnumerous types ofretail, those with the mostbanners, the largestandthe smallestinaverage size. Thecommercial densitybypostal codeis mappedandthe spatial variationsofthe commercial structureareanalyzedusingaprincipal components analysisandatypology. Theresultsarecomparedwiththe urban hierarchy.Theroleofpurchasing powerandtourismishighlightedasthedevelopment ofshopping centersandretail areas.